THE CONCEPT OF TARETAN DHIBI’ IN THE FRAME OF MADURESE RELIGIOUS MODERATION - Nor Hasan; Nurul Qomariyah (Islamuna: Jurnal Studi Islam, 2023)
Taretan dhibi' is one of the cultural enculturations of the Madurese people. This study attempts to investigate the Madurese people's cultural concept of the taretan dhibi’. The term taretan for Madurese people is the concept of relatives with the ideology of Madurese people who have a cultural obligation to maintain emotional interactions and kinship ties between one another. It is quite fascinating to study the concept of religious moderation due to the social style of Madurese society itself which is different from other regions. therefore, despite all of their distinctions in terms of religion, customs, and traditions, the author will look at how the Madurese people carry out the concept of taretan dhibi. Through descriptive phenomenological analysis, this research reveals that taretan dhibi' is a manifestation of the emotional ties between Madurese people. Thus, the form of religious moderation in the cultural concept of taretan dhibi' is firstly respecting brothers and sisters (mentioned in Madura as taretan) by allowig any kind of differences and providing space for self-expression. The concept of "taretan dhibi," which is entwined with Madurese society's religious moderation, is essentially the fundamental ideology of the Madurese people, which regards sincerity as the foundation of brotherhood. Second, appreciate and respect the part of the taretan concept that can equalize social positions among Madurese people. Third, the city of Pamekasan is a ideal example of the strength of the concept of taretan dhibi' within the framework of religious moderation in Madurese society. ABSTRAK Taretan dhibi’ adalah salah satu enkulturasi budaya masyarakat Madura. Tulisan ini mencoba menelusuri konsep budaya taretan dhibi’ dalam kehidupan masyarakat Madura. Istilah taretan bagi masyarakat Madura adalah konsep kerabat dengan ideologi masyarakat Madura yang memiliki kewajiban kultural untuk menjaga dan memelihara hubungan emosional dan silaturahmi ikatan kekerabatan antara yang satu dengan yang lainnya. Tergolong menarik untuk dikaji dengan konsep moderasi beragama, karena corak bersosial masyarakat Madura sendiri berbeda dengan daerah yang lainnya. Oleh karena itu, penulis akan mengkaji bagaimana Masyarakat Madura menjalankan konsep taretan dhibi’' dengan semua perbedaan yang ada di antara mereka, baik agama, kebiasaan dan tradisi. Melalui analisis fenomenologi deskriptif, penelitian ini mengungkapkan bahwa taretan dhibi’ adalah wujud dari adanya ikatan emosional antar masyarakat Madura. Oleh karena itu, wujud moderasi beragama dalam konsep budaya taretan dhibi’ adalah Pertama menghormati antar saudara (taretan) dengan mengakomodir segala bentuk perbedaan dan memberi ruang untuk mengekspresikan diri. Konsep taretan dhibi’ yang terjalin dalam moderasi beragama masyarakat Madura yakni pertama, ideology dasar masyarakat Madura yang menjadikan keikhlasan dan ketulusan sebagai dasar bersaudara. Kedua, menghargai dan menghormati bagian dari konsep taretan yang dapat menyamaratakan kedudukan dalam bersosial antar masyarakat Madura. Ketiga, kota Pamekasan menjadi contoh nyata kuatnya konsep taretan dhibi’ dalam bingkai moderasi beragama masyarakat Madura.